BALANCING ACADEMIC PERFORMANCE AND SPORTS ACHIEVEMENT IN SPECIAL SPORTS CLASS MANAGEMENT - Hidayah Uswatun Kasanah; Edi Purwanto; Akyas Shodiq Kurniawan; Siswanto, Deny Hadi (CV. Denasya Smart Publisher, 2025)
This study aims to provide an in-depth description of the management and development of the special sports class program at Muhammadiyah 1 Mlati Junior High School. A qualitative approach with a descriptive study design was employed. Data were collected through in-depth interviews, participatory observation, and document analysis involving the principal, physical education teachers, coaches, students, and other relevant stakeholders. The findings indicate that the program is managed based on key management functions: planning, organizing, implementation, and supervision. The coaching process is carried out systematically through a rigorous selection process, structured training, and academic support. Despite facing limitations in facilities, the school addresses these challenges through external collaborations. The program has had significant impacts, including improved student sports achievements at the national level, character development, and an enhanced school image. However, challenges remain, particularly the low academic motivation among some students, which requires further attention. The study concludes that the program has been implemented effectively and serves as a good practice model for talent and interest-based education, although regular evaluation and integrated curriculum enhancement are needed to maintain a balance between academic and non-academic achievements